2018
DOI: 10.1111/bcp.13535
|View full text |Cite
|
Sign up to set email alerts
|

Argon attenuates multiorgan failure following experimental aortic cross‐clamping

Abstract: Argon attenuated clinical and biological modifications of cardiovascular, renal and intestinal systems, but not the inflammatory response, after aortic cross-clamping. The window of administration was crucial to optimize organ protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…In addition, various studies investigating the indirect effects of IR on the small intestine using abdominal aortic clamping have found that IR is the result of the loss of villus epithelia. [25,26] In the present study, we observed intestinal ulceration due to intestinal epithelial loss. We also observed hemorrhage and the degeneration of intestinal crypts in subepithelial connective tissue.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, various studies investigating the indirect effects of IR on the small intestine using abdominal aortic clamping have found that IR is the result of the loss of villus epithelia. [25,26] In the present study, we observed intestinal ulceration due to intestinal epithelial loss. We also observed hemorrhage and the degeneration of intestinal crypts in subepithelial connective tissue.…”
Section: Discussionsupporting
confidence: 59%
“…Although the mechanism involved in pulmonary tissue damage following aortic occlusion is not fully understood, studies have shown that oxidative stress, in which an increase in ROS production and a decrease in antioxidant enzyme activation occur, may be the cause [ 11 , 24 ] . Kurtoglu et al [ 25 ] determined that aortic occlusion resulted in an increase in myeloperoxidase and MDA levels in serum and lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that abdominal I/R causes apoptosis in renal cells in addition to an increase in ROS [ 12 , 28 ] . In their study involving an aortic cross-clamping model in rats, Oyar et al [ 25 ] showed that in addition to increasing MDA levels in kidney tissue, I/R also led to apoptosis in renal tubule cells by increasing activity of Caspase-3, one of the caspases involved in the irreversible terminal stage of apoptosis.…”
Section: Discussionmentioning
confidence: 99%